How far are we? Assessing progress in hepatitis C response towards the WHO 2030 elimination goals by the civil society monitoring in 25 European countries, period 2020 to 2023 - Mojca Maticic; J. Cernosa; C. Loboda; J. Tamse; R. Rigoni; E. Duffell; I. Indave; R. Zimmermann; L. Darragh; J. Moura; A. Leicht; T. Windelinckx; et al. (Harm Reduction Journal)
Abstract Background With the advent of direct acting antivirals (DAAs) the World Health Organisation (WHO) adopted global strategy to eliminate hepatitis C virus (HCV) infection by 2030. In Europe, people who inject drugs (PWID) account for the majority of new cases, however testing and treatment remain suboptimal. The aim was to monitor progress in HCV policy and cascade-of-care for PWID, led by the civil society organisations (CSO) that provide harm reduction services for PWID across Europe. Methods In period 2020–2023, CSOs representing focal points of Correlation-European Harm Reduction Network were annually invited to complete online questionnaire on use/impact of HCV test-and-treat guidelines for PWID, availability/functioning of continuum-of-care, and role/limitations of harm reduction services for PWID. A retrospective longitudinal analysis of responses to questions answered each year by the same respondents was performed, and a comparison among the studied years was made. Results Twenty-five CSOs from cities in 25 European countries were included and responded to 25 questions. Between 2020 and 2023, there was positive trend in number of HCV treatment guidelines, separate guidelines for PWID, and their positive impact on acess to testing/treatment (24/25, 5/25, and 16/25 in 2023, respectively). DAAs were available in all countries, predominantly prescribed by specialist physicians only (slight increase at primary care), with restrictions including active drug use, stage of liver fibrosis or/and reimbursement policies (2/25, 4/25, and 3/25 in 2023, respectively). A decrease in HCV testing sites was noted. Treatment was consistently most common at clinical settings, however an increase outside the specialist settings was detected, particularly in prisons (12/25 and 15/25 in 2020–2021, respectively). Comparing 2022–2023, number of HCV-testing services increased in many cities with positive dynamic in nearly all the settings; increase in treatment at harm reduction services/community centres was noted (6/25 to 8/25, respectively). Between 2020 and 2023 the frequency of various limitations to CSOs addressing HCV was oscillating, presenting an increase between 2022 and 2023 (9/25 to 14/25, respectively). Conclusion The overall progress towards WHO HCV elimination goals across Europe remains insufficient, most probably also due to the influence of Covid-19 pandemic. Further improvements are needed, also by including CSOs for PWID in continuum-of-care services, and in monitoring progress.